The discursive use of the concept of 'corruption' in parliamentary debates during the Portuguese Estado Novo (1935–74) - Sousa, L.; Moriconi, M. (Rivista Italiana di Scienza Politica, 2015)
Corruption is deviant behaviour from legal and social norms, observable in both dictatorships and democracies, and salient in different periods of the history of mankind. Studying corruption in dictatorships is particularly challenging due to the fact that freedom of expression is censored and there is little (if any) reliable information about the enforcement of legal provisions. This article provides a contribution to the growing literature on the role of legislatures in dictatorships by focusing on parliamentary debates on corruption as a discourse control mechanism. The case of the Portuguese legislature during the Estado Novo is paradigmatic in that regard. The National Assembly, as it will be demonstrated in this article, was able to shift the debate on corruption from the legal to the moral dimension and, thus, deprive citizens, and in particular the opposition, of objective standards to hold regime elites accountable for their misconduct.